Saturday

August 2, 2014

August 2, 2014

Posted by **OH** on Sunday, November 3, 2013 at 4:13pm.

- Math -
**Ms. Sue**, Sunday, November 3, 2013 at 4:42pm5-(2x-1)=4(x+8)

5 - 2x + 1 = 4x + 32

6 - 32 = 6x

-26 = 6x

-26/6 = x

-4 1/3 = x

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

math - if (2x-3):(y+4)=k where k is a constant and x=4 when y=2 then find x when...

Math - 1. Solve (2x -3)< 14 2.Solve 3.2x + 20.8 > 52.0 -7.2x

math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...

Algebra - Need help with this problem, 2x+y=6 solve for y 2x+y=6 subtract 2x ...

How do I do this.?(Math.) - Use the Substitution method to solve the system of ...

Math - How do you do this question? I am not sure if this right. 1. solve ...

Math- Gr.12 - Solve and use set notation. a) 6+2x > 0 > -10+2x Can someone...

Math - Solving for Trig Equations - Solve the following equation for 0 less than...

Math-Trig - 1. Create an algebraic expression for sin(arccosx-arcsin3x) 2. The ...